2016
DOI: 10.1097/mnh.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Sodium glucose cotransporter 2 inhibition in the diabetic kidney

Abstract: Purpose of review The sodium glucose cotransporter SGLT2 reabsorbs most of the glucose filtered by the kidneys. SGLT2 inhibitors reduce glucose reabsorption thereby lowering blood glucose levels and have been approved as new anti-hyperglycemic drugs. While the therapeutic strategy is very promising, many questions remain. Recent findings Using validated antibodies SGLT2 expression was localized to the brush border of the early proximal tubule in human kidney and was found upregulated in genetic murine models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 50 publications
1
67
0
3
Order By: Relevance
“…Throughout the progression of diabetes, the kidney undergoes adaptive changes to accommodate and manage the increased filtered glucose load. These changes not only impact glucose handling but also contribute to the development and progression of renal damage and functional decline . The diabetic kidney is subject to tubular interstitial oxidative stress and inflammation with associated adaptive changes in renal function, biochemistry and pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the progression of diabetes, the kidney undergoes adaptive changes to accommodate and manage the increased filtered glucose load. These changes not only impact glucose handling but also contribute to the development and progression of renal damage and functional decline . The diabetic kidney is subject to tubular interstitial oxidative stress and inflammation with associated adaptive changes in renal function, biochemistry and pathology.…”
Section: Discussionmentioning
confidence: 99%
“…69 Interestingly, Pessoa et al recently reported that NHE3 activity is stimulated by luminal glucose, and that NHE3 co-localizes and may functionally interact with SGLT2 in the proximal tubule. Thus, it is possible that SGLT2 inhibition may inhibit NHE3 transport activity.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…SGLT2 inhibitors work independent of insulin and have little hypoglycemia risk. The compounds induce a modest diuresis/natriuresis, urinary calorie loss, and activation of lipolysis, which are associated with a modest reduction in body fat, body weight, and blood pressure [12]. Ongoing long-term clinical trials explore the safety and the clinical efficacy of SGLT2 inhibitors in the prevention of diabetic renal and cardiovascular complications [7-9, 11, 13].…”
Section: Introductionmentioning
confidence: 99%